2019
DOI: 10.3390/ijms20071656
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium from Human Mesenchymal Stromal Cells: Towards the Clinical Translation

Abstract: Mesenchymal stem/stromal cells (MSC) remain a promising tool for regenerative medicine as the efficacy of MSC-based cell therapy has been demonstrated for a broad spectrum of indications. Their therapeutic potency is mainly associated with their ability to secrete multiple factors critical for tissue regeneration. Due to comparable effects along with superior safety MSC conditioned medium (MSC-CM) containing a complex of MSC-secreted products is considered a reasonable alternative to cell therapy. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 62 publications
(69 reference statements)
1
96
0
5
Order By: Relevance
“…Adipose tissue is a major component of the breast tissue and is actively involved in forming TME; thus, adipose tissue through its inflammatory and lipogenic activities may increase the risk of BC development [3,40]. Human adipose CM is a source of various growth factors, several adipocyte secretory hormones, cytokines, and metabolites [41], which are immensely responsible for inducing expression of markers associated with breast cancer cell signaling, motility, and metastases [42,43]. Consistent with this, we have found increased inflammatory, IL-6, IL-8, NF-κB, and STAT3 mRNA expression as well as induced expression of the lipogenic enzyme FASN in both MCF-7 and MDA-MB-231 cells in response to human adipocyte CM.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is a major component of the breast tissue and is actively involved in forming TME; thus, adipose tissue through its inflammatory and lipogenic activities may increase the risk of BC development [3,40]. Human adipose CM is a source of various growth factors, several adipocyte secretory hormones, cytokines, and metabolites [41], which are immensely responsible for inducing expression of markers associated with breast cancer cell signaling, motility, and metastases [42,43]. Consistent with this, we have found increased inflammatory, IL-6, IL-8, NF-κB, and STAT3 mRNA expression as well as induced expression of the lipogenic enzyme FASN in both MCF-7 and MDA-MB-231 cells in response to human adipocyte CM.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, favorable data in this regard have kept pouring in to show that the secreted bioactive molecules are cytoprotective, anti-apoptotic, pro-proliferative, and effective in preconditioning of stem cells to support their cardiomyogenic differentiation [128][129][130]. Efforts are underway to develop a standard protocol for bioprocessing and quality control of the conditioned medium for optimal therapeutic usage [131]. The exosome-based strategy is fast-emerging as an alternative to the conditioned medium-based cell-free therapy approach [132].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Besides, one of the real issues is the use, in most of the studies reported, of FBS for the expansion of ASCs. Indeed, it is well known that this approach is not suitable for clinical use of ASCs or their secretome, due to the risk of transmission of disease as well as xenogeneic immune reactions in the transplanted host [33,86]. In this regard, recently, human serum albumin (HSA), human serum (HS), or knockout serum replacement (KSR) have been suggested as useful replacements of FBS for ASC cryopreservation and clinical banking [87].…”
Section: Discussionmentioning
confidence: 99%